LEVERAGING VIRTUAL INFLUENCER ATTRACTIVENESS TO GREEN PURCHASE INTENTIONS IN SUSTAINABLE FASHION - Sripoothorn, Khatesiree; Sittioum, Rattana (RMUTT Global Business and Economics Review, 2025)
Technological advancements have significantly impacted modern marketing strategies, with virtual influencers gaining increasing popularity. This study aims to examine the influence of virtual influencers’ attractiveness on consumers’ green purchase intentions, considering the mediating roles of attitude and brand engagement. A survey was conducted using a sample of 440 Thai consumers aged 18 and above, and the data were analyzed using the PROCESS Macro to explore the relationships between the variables. The results indicate that both attitude and brand engagement fully mediate the relationship between virtual influencers’ attractiveness and green purchase intention in a serial manner. However, the attractiveness of virtual influencers does not have a direct effect on purchase intention. The study highlights how the attractiveness of virtual influencers can enhance consumers’ positive green attitudes and increase brand engagement, ultimately leading to a higher green purchase intention. The findings contribute to the development of marketing strategies that utilize technology in sustainability businesses and expand the understanding of virtual influencer effects under the Stimulus-Organism-Response (S-O-R) theory.